School Closures and Parental Labor Supply - Ma. Christina F. Epetia; John Joseph S. Ocbina; Kimberly R. Librero (Philippine Institute for Development Studies (PIDS), 2023)
We explore in this study the potential impact of school closures to in-person learning on the labor supply of parents in terms of paid employment and hours of work. Using a probit model, we find that women with school-age children, regardless of educational attainment, face a lower probability to be on paid employment, but the same cannot be observed among men with school-age children. We also apply a Heckman model to estimate the log of hours of work. Conditional on employment, we see that school closures do not significantly determine the log of hours of work for both men and women with school-age children. However, further disaggregating the estimates by education reveals that female college graduates-and, to some extent, male college graduates-with school-age children tend to work more hours during school closures. In contrast, school closures appear to not affect the hours of work of less educated men and women with children. Overall, the results suggest that school closures have a negative effect on employment at the extensive margin for women, but there is no evidence on reduced labor supply at the intensive margins. Policies aimed at preserving employment and mitigating the deterioration of human capital can thus address the cost of school closures on women's labor supply.
Keywords: 330; labor supply; COVID-19 pandemic; school closures; gender differentials